Hubungan Mobilisasi Dini dengan Penyembuhan Luka Post Operasi Sectio Caesarea di Charitas Hospital Klepu - Margareta Melanie; Munica Rita H; Dyah Noviawati S.A. (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
One of the factors that influence the wound healing of a Caesarean section is early mobilization. Early mobilization can accelerate blood circulation so that oxygen supply to the tissues will be smooth and can accelerate the growth of new tissue in surgical wounds, improve metabolism regulation and restore the physiological work of organs vital organs. Purpose from the research to determine the relationship between early mobilization and postoperative wound healing at Cesarean Section at Charitas Hospital Klepu in 2021. This study used a cross-sectional design, this study was conducted in October 2020-March 2021. The study population of this study were mothers who gave birth with Caesarean section at Charitas Hospital Klepu, with a consecutive sampling technique of 33 respondents who were taken using. Data were collected through observation sheets, then analyzed using the chi-square test with a 95% degree of confidence. From the results of the study, 23 respondents (92%) had good early mobilization with good wound healing and 2 respondents (8%) had poor wound healing. Respondents who did poor early mobilization with good wound healing were 2 respondents (25%), while those who experienced poor wound healing were 6 respondents (75%). The results of statistical tests showed a relationship between early mobilization and postoperative wound healing (p = 0.001). Based on the results of the study, it can be concluded that there is a relationship between early mobilization and post-caesarean section wound healing